Teaching Proficiency through Reading and Storytelling (TPRS) as a Technique to Foster Students’ Speaking Skill - Muzammil, Lasim; Andy (JEELS (Journal of English Education and Linguistics Studies), 2017)
Teaching Proficiency through Reading and Storytelling (TPRS) is quite essential to improve EFL learners’ speaking ability. It can be done successfully by means of the basic concept of TPRS known as comprehensible input in second language acquisition (SLA). This paper presents a study on learners’ speaking ability through TPRS making use of three important steps; Showing, Telling, and Reading. This is a quantitative study using quasi-experimental as the two intact groups are used; experimental and control group. The data are obtained from pre-test, post-test and questionnaires viewed from both students’ and teachers’ perspective. The data from pre-test and post-test are analyzed by using independent sample t-test. The experimental and control are ascertained to be homogenous in term of English performance from the pre-test analysis. The post-test are carried out from both groups after the treatment and the the result of the test are compared in order to prove if the null hypothesis is rejected indicating that there is significant difference performance between the two groups. The result of the study is expected to be beneficial for English teachers, EFL learners, and further researchers.